2017
DOI: 10.1101/112979
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Developing a 670k genotyping array to tag ∼2M SNPs across 24 horse breeds

Abstract: Background

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…A recent study designed two chips for genotype imputation: MNEc670k, consisting of ~670k SNPs, and MNEc2M, a next‐generation HD SNP chip (~2 million SNPs). Genotype imputation accuracy from the MNEc670k SNP set to the MNEc2M SNP set ranged between 96.6% and 99.4% in the fifteen breeds tested (Schaefer et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study designed two chips for genotype imputation: MNEc670k, consisting of ~670k SNPs, and MNEc2M, a next‐generation HD SNP chip (~2 million SNPs). Genotype imputation accuracy from the MNEc670k SNP set to the MNEc2M SNP set ranged between 96.6% and 99.4% in the fifteen breeds tested (Schaefer et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…After these two medium‐density (MD) chips, a high‐density (HD) commercial chip, the Affymetrix Axiom Equine genotyping array (670k), was developed by the selection of 670,806 SNPs amongst the 2 million SNPs of an experimental chip designed from multiple breeds by the international consortium. This chip consisted of 626,710 new SNP markers and 44,096 SNPs already present on both MD chips (Schaefer et al., ). Currently, the Affymetrix Axiom Equine genotyping array and the Illumina Equine SNP70 BeadChip are the two commercial chips available.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 55 EPL samples genotyped on the Axiom™ Equine 670K SNP Genotyping Array [71] included 24 male and 51 female EPL conceptuses from Thoroughbred, Warmblood, and unknown breed pregnancies, with a spread of mare ages and gestational ages. Mare ages ranged from 3 to 21 years old.…”
Section: Methodsmentioning
confidence: 99%
“…This assembly was generated using the best genomic sequencing and assembly technologies available at the time, namely: Sanger sequencing, bacterial artificial chromosome (BAC) end pairs, radiation hybrid (RH) mapping, and fluorescence in situ hybridization (FISH) mapping. Since then, many researchers have used this reference genome to study the genetics of various traits in horses [3][4][5][6][7][8][9] , as well as their health [10][11][12][13] and evolution [14][15][16][17] . However, EquCab2 contains numerous gaps in scaffolds as well as sequences unassigned to chromosomes, and genomic DNA resequencing 18 and gene annotation 19 studies have found inconsistencies in this genome.…”
mentioning
confidence: 99%